The Role of Dividend Policy in Moderating the Effect of Profitability on Firm Value - Nola Velia Arizza; Muhammad Fajri Prasetyo (Global Sustainability Research Institute, 2026)
This study examines the effect of profitability on firm value and investigates the moderating role of dividend policy in the relationship between profitability and firm value while controlling for the debt-to-equity ratio and current ratio. A quantitative approach was employed using secondary data from 111 firm-year observations of publicly listed companies. Hierarchical moderated regression analysis (MRA) was applied after confirming that the data satisfied the classical assumption tests. The findings show that profitability, measured by Return on Equity (ROE), has a positive and significant effect on firm value, indicating that more profitable firms tend to achieve higher market valuations. Dividend policy does not have a significant direct effect on firm value. However, the interaction between profitability and dividend policy is significant and negative, suggesting that dividend policy weakens the positive impact of profitability on firm value. These results imply that while profitability serves as a positive signal to investors, higher dividend payouts may reduce the market's appreciation of profitability by limiting retained earnings available for future investment and growth opportunities. This study contributes to the corporate finance literature by demonstrating that dividend policy should be viewed not only as an independent determinant of firm value but also as a moderating factor that shapes the effectiveness of profitability in enhancing market valuation. The findings provide practical insights for managers in balancing profitability and dividend distribution to maximize shareholder value.